The method of chance in plastic art - KASSID, Hakima (Journal of Humanities & Social Sciences, 2022)
This research attempts to question the relationship between art and chance. Associating these two terms at first glance leads to a contradiction and requires in-depth investigation. Associating art with chance is a link between a random, involuntary phenomenon and a conscious intentional process, and their coexistence amounts to denying the artist’s complete control over his creative realization, which can lead to undermining the idea of genius and artistic inspiration, and casts doubt on the idea of hard work. However, with the emergence of modern art, artists began to express themselves with greater freedom, and they resorted to chance and its methodological and unsystematic mechanism, so they surrendered to it and ceased to fight it, and submitted it to their ultimate ends and intentions, which opened the door for the artist to experience the sensory world of an infinity in order to obtain surprising and amazing results.